The Dual Role of Arab League Mediation in the Yemen Conflict: A Comparative Analysis of Regional Actors (2015–2024) - Canon, Juan; Napitupulu, Kevin Jonathan M.; Ramadhanny, Syifaniar; Trisnaningtyas, Januari Pratama Nurratri (Journal of Integrative International Relations, 2026)
This study argue that the Arab League’s role in the Yemeni conflict during the 2015-2024 period was ambivalent, serving both as a meidator supporting the peace procces and as a political actor involved in regional conflict dynamics. The research method employed is comparative analysis within the framework of conflict resolution theory, comparing the roles of the Arab League, the United Nations (UN), and the Gulf Cooperation Council (GCC) based on four key variables: neutrality, institutional capacity, political and material leverage, and the inclusivity of the mediation process. The analysis revelas that the Arab League’s involvement exhibits a contradictory dual pattern that limits the effectiveness of sustained mediation, despite the League possessing regional legitimacy and the capacity to drive peace initiatives. In comparison, the UN demonstrates a superios position in terms of neutrality and institutional capacity, while the GCC is resilient in regional leverage but limitied its relience on mediation. Various interests among Arab League members and the organization’s limited capacity pose the primary challenges in the conflict mediation process. Lessons drawn from this experience highlight the importance of stronger coordination and a comprehensive approach that includes all relevant stakeholders in order to achieve sustainable peace.